UHPLC-MS characterisation of principal triterpene glycosides and biological activities of different solvent extracts of Allochrusa gypsophiloides (Caryophyllaceae) - Mamadalieva, Rano; Xujayev, Vaxobjon; Sharopov, Farukh; Wink, Michael (Natural product research, 2023)
A crude methanol extract of the roots of Allochrusa gypsophiloides (syn. Acanthophyllum gypsophiloides) (collected from the Tashkent region of Uzbekistan) was chemically characterised by UHPLC-ESI-QTOF-MS/MS analysis. The results indicate the presence of six major bisdesmosidic saponins derived from gypsogenin, gypsogenic and quillaic acids, including five compounds reported for the first time for this species. The chloroform, methanol and water extracts of A. gypsophiloides showed weak antioxidant and anthelmintic activities. Among the tested extracts, the water extract exhibited the highest level of cytotoxicity in CCRF-CEM and CEM/ADR5000 cell lines with IC50 values of 23.6 and 31.9 µg/mL, respectively.